Предмет: Алгебра,
автор: darinamango
a^2+b^2/a^2-b^2-a-b/a+b
Помогите пожалуйста упростить
Ответы
Автор ответа:
0
(а^2+b^2)/(a^2-b^2) - (a-b)/(a+b) = =(а^2+b^2)/(a^2-b^2) - (a-b)^2/((a+b)(a-b)) = = [(а^2+b^2) - (a-b)^2]/(a^2 - b^2) = = [а^2+b^2 - a^2 + 2ab - b^2]/(a^2 - b^2) = = 2ab/(a^2-b^2)
Похожие вопросы
Предмет: Английский язык,
автор: jisoovirt
Предмет: Русский язык,
автор: Аноним
Предмет: Обществознание,
автор: valeevstepan7
Предмет: Экономика,
автор: Дарья85365
Предмет: Литература,
автор: ayanaalisa